Managing the Paradoxes of Place to Foster Regeneration. (December 2021) - Slawinski, Natalie; Winsor, Blair; Mazutis, Daina; Schouten, John W.; Smith, Wendy K.
Organizations face and contribute to mounting social problems and environmental degradation. Regenerative organizations seek to reverse this damage, emphasizing how to help local places flourish. Drawing on a six-year inductive study of one such regenerative organization, we derive an empirically grounded model which argues that regeneration depends on effectively managing place-based tensions paradoxically. Shorefast built social enterprises aimed at redeveloping the cultural and economic resilience of Fogo Island, Canada, a community devastated by the collapse of the North Atlantic cod fishery. They triggered place-based tensions and managed them paradoxically by creating conditions for meaningful exchange and by taking a patient approach. Together, these efforts facilitated both the discovery of place-based opportunities and the regeneration of place. Our model challenges organizational researchers studying place to move beyond considering place-based tensions as conflicts and, instead, to study their paradoxical nature and management. To paradox research, we contribute insight into paradoxes of place.